Critical Transitions in Ecosystems and Society. The Contribution of Sociological Systems Theory to the Analysis of Socio-Environmental Transformations - Mascareño, Aldo (Frontiers in Sociology, 2022)
The theory of critical transitions and the theory of self-referential social systems are two well-established theories in the ecosystem and sociological research respectively. A dialogue between them may offer new insights on the complex articulation of the nature and society nexus in socio-environmental transformations. By means of a conceptual reconstruction of both theories and drawing on relevant literature of social-ecological research, in this article, I argue that systems theory can contribute to the theory of critical transitions with a robust concept of communication that accounts for the relevance of semantics and social structures, the production of communicative locks, and the identification of early warning signals of social-ecological transitions in communication. On the other hand, the theory of critical transitions provides systems theory with both a refined concept of crisis as critical transition and the technical tools for empirical research. The article concludes that the dialogue between the science of ecosystems and the science of society is not an intellectual exercise but a form of increasing the correspondence between social-ecological transitions and our explanations and interventions in this domain.